1995
DOI: 10.1161/01.cir.92.3.606
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Placement of Aortopulmonary Shunts

Abstract: In utero placement of aortopulmonary shunts reproduces the aberrant hemodynamic state of children with cogenital heart disease with left-to-right shunts; postnatal pulmonary hypertension, increased pulmonary blood flow, and vascular remodeling. In addition, the lambs have a unique paradoxical increase in pulmonary vascular volume that attenuates an increase in pulmonary vascular resistance. This experimental preparation provides a useful and consistent model for the study of the pathogenesis of pulmonary hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 137 publications
(84 citation statements)
references
References 24 publications
1
82
1
Order By: Relevance
“…At 1 month of age, these lambs have a pulmonary-to-systemic blood flow ratio of Ϸ2:1, a mean pulmonary arterial pressure that is 50% to 75% of mean systemic arterial pressure, and pulmonary vascular remodeling characteristic of children with pulmonary hypertension and increased pulmonary blood flow. 12 Previously, we demonstrated that these lambs display alterations in the ET-1 cascade at 4 weeks of age. These include increased plasma ET-1 levels, decreased ET B receptor protein with loss of ET B receptor-mediated vasodilation, and increased ET A receptor protein with augmentation of ET A receptor-mediated vasoconstriction.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…At 1 month of age, these lambs have a pulmonary-to-systemic blood flow ratio of Ϸ2:1, a mean pulmonary arterial pressure that is 50% to 75% of mean systemic arterial pressure, and pulmonary vascular remodeling characteristic of children with pulmonary hypertension and increased pulmonary blood flow. 12 Previously, we demonstrated that these lambs display alterations in the ET-1 cascade at 4 weeks of age. These include increased plasma ET-1 levels, decreased ET B receptor protein with loss of ET B receptor-mediated vasodilation, and increased ET A receptor protein with augmentation of ET A receptor-mediated vasoconstriction.…”
mentioning
confidence: 86%
“…[12][13][14] Through a left lateral fetal thoracotomy, an 8.0-mm Gore-tex vascular graft (Ϸ2 mm long) (W.L. Gore and Associates) was anastomosed between the ascending aorta and main pulmonary artery of the fetus with 7.0 proline (Ethicon Inc) with a continuous-suture technique.…”
Section: Ewesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight pregnant, mixed-breed Western ewes (135-140 days gestation; term ϭ 145 days) were operated on under sterile conditions. Through a left lateral fetal thoracotomy, an 8.0-mm Gore-Tex vascular graft (2-mm length; W. L. Gore, Milpitas, CA) was anastomosed between the ascending aorta and main pulmonary artery, as previously described in shunted lambs (52). After the surgery, the ewes were returned to the cage with free access to food and water.…”
Section: Surgical Preparations and Carementioning
confidence: 99%
“…One important form of nonsprouting angiogenesis is intussusception, first described by Burri and coworkers (Caduff et al, 1986;Burri and Tarek, 1990) in the capillaries of the pulmonary circulation. At certain periods of postnatal pulmonary development, and in instances of pathophysiological increase of blood flow, the pulmonary circulation demonstrates an intrinsic capacity to increase arterial and venous vessel number by an unknown mechanism of angiogenesis (Reid and Davies, 1988;Reddy et al, 1995). Another important process that is not presently understood, especially during stages of pulmonary hypertension development, is the phenomenon of "pruning," i.e., obliteration and removal of branches from a bifurcation (Reid and Davies, 1988).…”
Section: Introductionmentioning
confidence: 99%